Inclusión y su incidencia en el desarrollo socioeconómico de las personas con condiciones especiales del centro de dirección de gestión de desarrollo social en el cantón quevedo año 2023 - Tenorio Quiñonez, Diana Carolina (2025)
The research addresses inclusion and its impact on the socioeconomic development of people with special conditions of the Social Development Management Management Center in the Quevedo canton. The justification of this research document lies in the need to strengthen the implementation of programs that promote the social and economic integration of this group, considering its positive impact on the quality of life and social cohesion. The main objective was to determine the incidence of inclusion in the socioeconomic development of people with special conditions of the Social Development Management Management Center in the Quevedo canton in 2023 in order to propose improvements in the management of the services offered by this institution through its programs. The methodology included an analytical, inductive and deductive approach. A survey was carried out on 60 users who used this service and an interview with the center coordinator in the area of special conditions. These tools allowed key data to be collected on the needs and perceptions of beneficiaries. Among the most notable findings, it was identified that coordination between institutions and the community is crucial for the sustainability of the programs. However, the absence of financial and human resources was evident, which limits its effectiveness. It is concluded that it is imperative to optimize program management through strategies that guarantee greater availability of resources and a more inclusive and participatory approach, thus promoting a stronger socioeconomic impact on beneficiaries.